LECT2, A Novel and Direct Biomarker of Liver Fibrosis in Patients With CHB - Xu, Honghai; Li, Xutong; Wu, Zihao; Zhao, Linyan; Shen, Jiapei; Liu, Jiaying; Qin, Jiangfeng; Shen, Yuanlong; Ke, Jing; Wei, Yuanyuan; Li, Jiabin; Gao, Yufeng (Frontiers in Molecular Biosciences, 2021)
Chronic hepatitis B (CHB) patients with severe liver fibrosis would more likely to progress to a poorer prognosis. Treatment is considered once the liver fibrosis reaches significant liver fibrosis (S2). Leukocyte cell-derived chemotaxin-2 (LECT2) has been shown to contribute to liver fibrosis progression. No researches had focused on the role of LECT2 in liver fibrosis in CHB patients. This study enrolled 227 CHB patients and divided them into the training group (n=147) and validation group (n=80), respectively. The expression of LECT2 in serum, protein and mRNA of the human liver tissues was detected to analyze the possible associations between LECT2 and liver fibrosis. A receiver operating characteristic curve (ROC) was used to estimate the efficacy of LECT2 for predicting liver fibrosis. The data showed that there was a positive relationship between LECT2 and the progression of liver fibrosis. In the training group, LECT2 was demonstrated to have better effectiveness than APRI and FIB-4. The AUC was 0.861, 0.698, and 0.734 for significant liver fibrosis, and 0.855, 0.769, and 0.752 for advanced liver fibrosis. Besides, the efficacy of LECT2 in different statuses of patients with CHB was examined and the effectiveness of LECT2 had also been confirmed in the validation group. All the results confirmed that LECT2 could act as a perfect predictor and thus offers a novel and direct biomarker to estimate liver fibrosis more accurately.